TINJAUAN YURIDIS ASIMILASI PADA LEMBAGA PEMASYARAKATAN TERBUKA (Studi di Lapas Terbuka Kelas IIB Mataram) - Kusuma, Jauhari Dwi (Fakultas Hukum Universitas Nahdlatul Wathan Mataram, 2019)
One of the places inmates undergo assimilation is by being placed in the open prison. Placement of Prisoners in Open Prison must meet certain requirements other than those generally regulated in Government Regulation Number 32 of 1999 Concerning the Terms and Procedures for the Implementation of Prisoners' Rights as last amended by Government Regulation Number 99 of 2012 there are also special arrangements in Circular Director General of Corrections Number E.PK.04.10-115 and Number PAS-PK.01.01.02-100 regarding the placement of prisoners to the Open Penitentiary Institution / Agricultural Camp. From the results of the analysis of these laws and regulations the obstacles to the placement of Prisoners in Open Prison are as follows: 1) The assimilation requirements in the form of Community Research (LITMAS) are a long process due to the limitations of the Community Guidance Officer, 2) Procedurally the process is long; 3) The location of the Lapas Lapas is far from the prisoner's house; 4) Appropriate assessment process according to criteria is very difficult. For the implementation of Assimilation in the Mataram Open Prison, in practice it is in accordance with the Decree of the Minister of Justice of the Republic of Indonesia NO.M.02-PK.04.10 of 1990 concerning the Pattern of Prisoners / Detainees in the form of 2 fields, namely the Development of Personality and Independence.